Development of a low-cost smart parking solution for smart cities - Fernandes, J. (2018)
The pressure of traffic on modern cities keeps growing. More and more vehicles flow into the city draining the existing parking resources and increasing traffic congestions and fueling the pollution increase. In this paper we present a solution for a low-cost smart parking system and all the software and hardware components that were developed and integrated in a smart parking prototype. The developed prototype is based on Arduino for the sensor network and on the Raspberry Pi for the gateway device. This paper also describes some of the technology aspects used in the communication between the sensors and the gateway – based on the ZigBee protocol. In addition to the hardware part of the prototype, the used backend architecture and the mobile application, that enables the user to find quickly and efficiently a parking spot, are also analyzed in this paper.